2016
DOI: 10.1002/wcms.1281
|View full text |Cite
|
Sign up to set email alerts
|

Application of quantum mechanics/molecular mechanics methods in the study of enzymatic reaction mechanisms

Abstract: Quantum mechanics/molecular mechanics (QM/MM) methods offer a very appealing option for the computational study of enzymatic reaction mechanisms, by separating the problem into two parts that can be treated with different computational methods. Hence, in a QM/MM formalism, the part of the system in which catalysis actually occurs and that involves the active site, substrates and directly participating amino acid residues is treated at an adequate quantum mechanical level to describe the chemistry taking place.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 230 publications
(448 reference statements)
2
118
0
Order By: Relevance
“…To determine the enzymatic mechanism of hPDI, we used QM/MM calculations with the our own N-layered integrated molecular orbital/molecular mechanics (ONIOM) methodology (80). Nevertheless, several different computational approaches have been widely used to determine enzyme reaction mechanisms (81)(82)(83)(84)(85)(86)(87)(88)(89)(90). We have drawn thermochemical and kinetic insight from single-conformation calculations with the X-ray-based model.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To determine the enzymatic mechanism of hPDI, we used QM/MM calculations with the our own N-layered integrated molecular orbital/molecular mechanics (ONIOM) methodology (80). Nevertheless, several different computational approaches have been widely used to determine enzyme reaction mechanisms (81)(82)(83)(84)(85)(86)(87)(88)(89)(90). We have drawn thermochemical and kinetic insight from single-conformation calculations with the X-ray-based model.…”
Section: Methodsmentioning
confidence: 99%
“…The mPW1N/ 6-31G(d):FF99SB level of theory was used for all geometry optimizations. Several works have shown that the 6-31G(d) basis is adequate for the purpose (85). Furthermore, a previous study has shown that mPW1N (96)(97)(98)(99)(100)(101) [along with mPW1K (96-100, 102, 103), BB1K (104)(105)(106), and mPWB1K (96-100, 104, 107, 108)] is one of the best density functionals to adequately describe the thermochemistry and kinetics of thiol-disulfide exchange (45).…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the rest of the protein environment was considered with the CPCM implicit solvation model using a dielectric constant of ε = 4.0, as suggested by Himo and co-workers [28], and a dielectric constant of ε = 78.4 for the aqueous solution, all in line with our previous reports [13], where we also demonstrated that a potential increase in the former dielectric constant to ε = 20.0 lowers the accuracy of the obtained results and even predicts wrong trends among ligands. Additionally, in our experience, such a truncated cluster-continuum model of the entire protein turned very useful in rationalizing various aspects of the catalytic activity [29], selectivity [30] and inhibition [31] of the monoamine oxidase family of enzymes, and is broadly used by different groups to decipher various biological phenomena [32][33][34][35][36], which justifies its use here. We note in passing that, despite its practical usefulness, the proposed value of ε = 4 is, in some cases, apparently too small to prevent the proton transfer from protonated to anionic residues, which then occurred spontaneously during the geometry optimization, provided the involved pair is in close vicinity.…”
Section: Computational Detailsmentioning
confidence: 98%
“…Multiple applications have shown that, when applied sensibly and appropriately, QM/MM calculations can provide insight and can make useful predictions, [115][116][117][118] and e.g. identify catalytic interactions 119, 120 .…”
Section: Acs Paragon Plus Environmentmentioning
confidence: 99%